Ethical, legal, and policy dimensions and contentions for reanalysis and reinterpretation of clinical genetic testing results - Sentell, Zachary T.; Zawati, Ma’n H. (Frontiers in Genetics, 2025)
The rapid evolution of genomic knowledge has made reanalysis and reinterpretation of clinical genetic testing results an ethical imperative to ensure optimal patient care. However, significant discrepancies persist between policies, laboratory practices, and stakeholder perspectives regarding the responsibility for initiating and communicating reclassified variants. This perspective examines the current landscape of ethical, legal, and practical challenges for laboratories, clinicians, and patients. We highlight the tension between the duty of care and resource constraints, finding that while the ethical importance of reinterpretation is acknowledged, the lack of standardized guidelines and legal clarity fuels uncertainty and discordant stakeholder views. To address these challenges, we propose an actionable, shared-responsibility framework that aligns duties with expertise. In this model, diagnostic laboratories are positioned to monitor new evidence and initiate updates for reinterpretation, while clinicians manage patient recontact and initiate case-level reanalysis, and health systems provide the necessary infrastructure. Realizing this framework through multidisciplinary collaboration and investment is crucial for establishing equitable best practices and integrating reinterpretation into the evolving standard of care.